Study guides

☆☆

Q: Factor 2x squared plus 2x plus xy plus y?

Write your answer...

Submit

Still have questions?

Related questions

4

0

2 (2x2 + 2x + xy + y ) it's 2 (2x + y)(x + 1) if you're doing A+

(x - 1)(2x + y)

x2y + axy + abx + a2b Factor by grouping. xy(x + a) + ab(x + a) (xy + ab)(x + a)

xy plus 2x plus 4y plus 8 or (xy+2x) + (4y+8) or x(y+2) + 4(y+2) or (x+4)(y+2)

Divide by 'x'; x2+xy/x = x(x+y)

(x + 4)(y - 2)

(x + 4)(y - 2)

(x + 4)(y - 2)

xy(3x - 2y)(2x + 3y)

The only common factor to all terms is yz. → xy³z² + y²z + xyz = yz(xy²z + y + x)

xy-2x+4y-8 x(y-2)+4(y-2) (x+4)(y-2)

0

(y-2) (x+4)

The GCF is xy

(2x - 3y)(x + y)

If that's xy + x^2y, it factors to xy(x + 1) If it's something else, please re-submit your question with any plus signs written out.

( 2xy - 4x ) + ( 8y - 16)2 ( xy - 2x ) + 2 ( 4y - 8 ) Answer

x(y - 1)(y + 1)

Factor by grouping. x2y - xyb - abx + ab2 The first two can factor out an xy, so xy(x - b) The second two can factor out a -ab, so -ab(x - b) and we have xy(x - b) - ab(x - b) Since what is inside the parentheses is alike, we can be assured that we have factored correctly and now continue to group: ANS: (x - b)(xy - ab)

The GCF is xy.

x+y

y=f(x)= x(2x+y)=7 f(x)=2x^2 +xy -7 = 0 y=2x^2 +xy -7 y-xy -7 + 2x^2 = 0 y(1-x)=2x^2-7 y=(2x^2-7) / (1-x) Excuse the working. Y equals 2 X squared minus 7 all divided by 1-X

2+2y+x+xy=(x+2)(y+1)